Bacterial flora of the genital tract in pregnancy and early labour - Sule-Odu AO; Akadiri AA; Oluwole AA; Osinupebi OA; Andu BA; Akiseku AK; Lawal AI; Oritogun KS (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Bacterial infections of the reproductive tract are common during pregnancy and have been associated with some pregnancy-related morbidities. There is limited information on the prevalence of bacterial infection of the reproductive tract during labour. Objective: To compare the prevalence of bacterial colonisation of the reproductive tract of pregnant women in early third trimester and early labour, and determine the associated foetal outcome. Methods: High vaginal swabs were collected from 201 pregnant women with gestational age from 26 to 32 weeks at the antenatal clinic of a Nigerian teaching hospital. The samples were processed to isolate bacterial organisms. Repeat samples were collected in early labour. The foetal outcome was assessed and recorded. Results: The prevalence of bacterial colonisation was 31.3% in early third trimester and 21.9% in early labour (p = 0.032). Staphylococcus aureus was the most prevalent organism isolated. Cefoxitin and imipenem were the most sensitive antibiotics. Women who had positive bacterial cultures in pregnancy had a slightly higher risk of low birth weight babies (RR 1.9, CI 0.9-3.7) and neonatal hospitalization (RR 1.8, CI 0.9-3.4) but without statistical significance (p = 0.05, and p = 0.06 respectively). Conclusion: The prevalence of bacterial colonisation of the reproductive tract of pregnant women was significantly higher in early third trimester than in early labour. There was no significant difference in pregnancy outcome between women who had positive bacterial cultures and those with negative cultures.